TANGGUNG JAWAB PENERIMA KUASA JUAL MENGACU PADA AKTA KUASA JUAL DIBUAT OLEH NOTARIS DALAM HAL PERALIHAN HAK ATAS TANAH - Winda Lestari Hasan (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe power to sell, is included in the category of power that is used to transfer the object that can only be done by the owner. Therefore, for the power of attorney to sell, a power of attorney is required in the presence of express words in the act. In practice, there are still found power recipients who do not directly complete the tasks given by the Authorizer. Even the power of attorney exercises the power of attorney within a period of time long after the power of attorney is signed by both parties. The problem raised in this paper is how the responsibility of a power of attorney in the transfer of land rights and what are the legal constraints of the power of attorney in the process of transferring land rights by using a sales authorizationThis type of research is normative juridical research, library research with the problem approach used in writing this thesis is the statute approach.The results showed that the responsibility of a power of attorney is to be based on the power of attorney that he has made and must immediately implement the power granted by the power of attorney and the constraint of the power of attorney in the process of transferring land rights by using a power of attorney ie selling a power of attorney not made notaryly but under the hand, incapable of accepting power of attorney, authorization of more than one person so that must require the agreement of all the power of attorney. Keywords: responsibility, power of attorney, land rights party